INOVASI PENDIDIKAN ISLAM MUHAMMAD ABDUH - Daulay, Maslina (IAIN Padangsidimpuan, 2013)
Muhammad Abduh was a monumental figure and the most eager to do an update for the Islamic world, especially Islamic education. He was a person who was successful in opening the doors of ijtihad to adjust to the demands of modern-day Islam. Muhammad Abduh focused on education reform. This was consistent with his purpose of life. This method was an effort to reform. It was due to the use of the proper functioning of the brain or mind. Thus, the activity of thinking could produce a science to suit the times.